Cultural Observatories as Digital Platforms of Public Value in Brazil: A Comparative Analysis - Ribeiro, Silvia B.; Macadar, Marie Anne; Pinto, Fernando (Conference on Digital Government Research, 2025)
For enhancing transparency and compliance with access to information laws, government portals provide information about investments, investing companies, and beneficiary sectors in creative economy. However, the dispersion and poor structuring of data on government investments in culture limit the understanding of the public value generated by these actions, both for public managers themselves and for society. Based on an empirical quantitative study with collected data frow digital portals of two Brazilian different subnational states, this article aims to discuss how government portals can structure their data on cultural investments in a way that translates its public value. As results, we propose directives for the structuring of culture data in government platforms that contemplates dimensions in a way that supports the perception of public value.